Study of the possibility of using agricultural wastewater for the accumulation of microalgae biomass. (International Journal of Biology and Chemistry, 2023)
The article examines the possibilities of using various agricultural wastewater for the accumulation of biomass of microalgae Chlorella vulgaris SP BB-2, Parachlorella kessleri Bh-2 and Chlamydomonas reinhardtii Dangeard CC-124. As a result of the study, a strain of microalgae C.vulgaris SP B-2 was selected for use in the treatment of fishery wastewater with the possibility of obtaining feed biomass. According to the research results, this strain showed an increased growth rate in aquaculture wastewater, also the effectiveness of reducing the COD index, removing ammonia and phosphates. According to the results of the study, the protein content in the resulting biomass of C-vulgaris SP BB-2 was 57.0 ± 1.2%, lipids 16 ± 1.2% and carbohydrates 11.4 ± 1.4% when grown on wastewater. The strain of C.vulgaris SP BB-2 can be effectively used in the bioremediation of wastewater in order to purify it from organo-mineral contaminants